Reconstruction of Qiwāmah in a Dual-Income Muslim Family: An Analysis of Maqāṣid al-Syarī'ah and Tahqīq al-Manāṭ against QS. an-Nisā' Verse 34 - Darliswanto; Muhammad Aldi Wahyu (International Journal of Social Sciences and Humanities, 2026)
The concept of qiwāmah in Qur'an Surah al-Nisā' verse 34 has long been regarded as a central principle in Islamic family law, traditionally understood as the basis of the husband's leadership within the family. However, the emergence of Muslim dual-income families has raised questions regarding the relevance of this concept amid changing economic structures and marital relations. This study aims to analyze the construction of qiwāmah in Qur'an Surah al-Nisā' verse 34 from the perspectives of classical Qur'anic exegesis and Islamic jurisprudence, examine the relevance of its underlying foundations within contemporary Muslim dual-income families, and formulate a reconstruction of qiwāmah through the approaches of maqāṣid al-sharī'ah and taḥqīq al-manāṭ. This research employs a normative Islamic legal research design using uṣūl al-fiqh approaches, particularly taḥqīq al-manāṭ and maqāṣid al-sharī'ah. Primary sources include the Qur'an, classical and contemporary tafsir works, fiqh literature, and uṣūl al-fiqh texts, while secondary sources consist of scholarly books and journal articles. Data were analyzed using descriptive-analytical methods. The findings reveal that classical understandings of qiwāmah are based on three principal manāṭ: leadership capacity, financial responsibility, and family protection. Through taḥqīq al-manāṭ analysis, this study finds that these three foundations remain present within Muslim dual-income families, although their practical implementation has undergone significant transformation. Based on maqāṣid al-sharī'ah, this study reconstructs qiwāmah as a family leadership responsibility oriented toward public welfare (maṣlaḥah), implemented through cooperation and consultation between spouses, and aimed at ensuring family stability, protection, and well-being. These findings suggest that qiwāmah remains relevant in contemporary Muslim families when interpreted contextually in light of the objectives of Islamic law.